The level of psychological compatibility in light of some variables among the apprentice teenager - chikh, rekia; telemsani, fatima (Journal of Social Sciences and Humanities, 2024)
This study aimed to explore levels of psychological compatibility among teenagers in vocational training centers in Saida state, examining various dimensions including emotional, health, family, and social aspects. Using a descriptive analytical approach and a psychological compatibility questionnaire developed by the researcher, data were collected from a sample of 200 male and female teenagers. The results of the study revealed that the levels of the four dimensions varied between low, medium, and high. Health compatibility emerged as the highest, followed by emotional compatibility. Additionally, adolescents demonstrated moderate to high levels of social and family compatibility. Gender differences were found to be non-significant. The study discusses its findings within the context of existing literature and theoretical frameworks, concluding with insights, observations, and suggestions based on the results.